Design of a relative value unit-based tool for the measurement and reimbursement of pharmacy services for clinical trials. Issue 4 (28th February 2018) - Pagès-Puigdemont, Neus; Molas, Glòria; Gorgas, Maria Queralt; Berga, Núria; Codina, Carles; Cruel, Miquel; Gómez-Perez, Begoña; Espona, Mercè; Rodríguez-Arias, Ainhoa; Salas, Esther; Mangues, Maria Antònia
Abstract : Objective: To develop a relative value unit ( RVU)-based tool for the measurement and reimbursement of pharmacy services for clinical trials. Methods: A portfolio of activities was agreed by consensus in four tertiary hospitals. Related activities were pooled into several categories or intermediate products. We recorded the duration of each activity by multiple determinations. We then calculated the average time of all determinations. The reference activity was assigned a value of 1. All other activities were compared to the reference activity to obtain the RVU. To establish which items should be invoiced to third parties for the activities performed, we defined the final products (different types of clinical trials according to their complexity). Results: Ten intermediate products and five final products were differentiated. Six intermediate products could be repeated over the course of a clinical trial and seven were performed whether or not the clinical trial had included patients. Each final product consisted of different categories. The total number of RVUs produced for a clinical trial was the sum of each constant category value plus the repetitive category values multiplied by the number of repetitions. Conclusion: The application of RVU methodology in investigational drug services allows a more precise quantification of services performed. After a prospective validation to confirm the applicability of this tool, it may contribute to more appropriate invoicing to third parties for these services.